Risk factors of early childhood caries (ECC) among children in Beijing - a prospective cohort study - Can Can Fan; Wen Hui Wang; Tao Xu; Shu Guo Zheng (BMC, 2019)
Abstract Background Early childhood caries (ECC) was a serious oral health concern with high prevalence and a low treatment rate in China, and few researches have focused on preschool children. This study aimed to explore the risk factors of ECC in Beijing, China. Methods Totle of 712 children (mean age: 46.37 ± 5.44 months) participated in this prospective cohort study. Questionnaires and the levels of mutans streptococci in dental plaques and non-stimulated saliva, assessed using Dentocult SM strips, were collected at baseline, respectively. Two calibrated examiners checked for dental caries according to the WHO 1997 criteria at baseline and 1-year follow-up. Negative binomial regression was used for multivariate analysis of factors related to caries development. Results For caries-free children at baseline, only plaque mutans streptococci (PMS) levels were associated with caries development (odds ratio [OR] = 1.68, 95% confidence interval [CI]: 1.08-2.61, P = 0.02). Children with high PMS levels (scored 2 and 3) had higher caries incidence (46.2% vs. 33.8%) and more caries increment (1.87 ± 3.17 vs. 0.90 ± 1.89) than those with low levels (scored 0 and 1). Among all participants, PMS (OR = 1.69, 95% CI: 1.32-2.23, P < 0.001) and previous caries experience (OR = 2.80, 95% CI: 2.20-3.56, P < 0.001) were related to caries increment. Conclusions For caries-free children, the only significant risk factor for ECC was high PMS levels. For all participants, besides high PMS levels, previous caries experience was another significant risk factor for caries development. Trial registration The study design, protocol, and informed consent forms were undertaken with the understanding of Declaration of Helsinki and were approved by the Human Research Ethics Committee of the School of Stomatology, Peking University, China (PKUSSIRB-2012042).